2007
DOI: 10.1002/eji.200636569
|View full text |Cite
|
Sign up to set email alerts
|

Categorical selection of the antibody repertoire in splenic B cells

Abstract: In the bone marrow, the passage of developing B cells through critical checkpoints of differentiation is associated with a reduction of specific categories of CDR3 of the Ig heavy chain (CDR-H3), particularly those with excessive hydrophobic or charged amino acids and those with a length of eight or fewer residues. To gain insight into the role of CDR-H3 content in the development of B cells in the spleen, we compared the sequences of V H 7183DJCl transcripts from sorted transitional T1, marginal zone, and fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 44 publications
(71 reference statements)
5
70
2
Order By: Relevance
“…Data presented herein show that so-called "polyclonal B cell activation" in this viral infection is instead selective expansion of B cells with hydrophobic HCDR3s that are normally deselected during development (75) to yield an oligoclonal population with hydrophobic HCDR3s. This biased expansion means that the normally dominant, neutral-charged HCDR3 population seen in newborns and other treatment groups (Fig.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Data presented herein show that so-called "polyclonal B cell activation" in this viral infection is instead selective expansion of B cells with hydrophobic HCDR3s that are normally deselected during development (75) to yield an oligoclonal population with hydrophobic HCDR3s. This biased expansion means that the normally dominant, neutral-charged HCDR3 population seen in newborns and other treatment groups (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…These investigators show that in the mature B cell repertoire, glycine and tyrosine primarily encoded in RF1 are overrepresented and this effect is responsible for the near neutral (0.0 -0.3) population (64). Hydrophobic HCDR3s are found in the T1 repertoire and the immature B cells from which they are derived, but this population is selectively lost in mature, circulating B cells (75).…”
Section: Discussionmentioning
confidence: 99%
“…3A). This is in contrast to the mouse preimmune repertoire, where the HCDR3 length ranges from five to 20 codons (average ϳ12.5 codons) (36). It is well established that upon encountering the Ag the HCDR3 length range typically narrows down, as a restricted set of CDR3 lengths provides optimum Ag binding.…”
Section: Cdr3 Length and Compositionmentioning
confidence: 88%
“…Ig molecules that bind B cell epitopes found on the surface of soluble Ags by necessity tend to be hydrophilic. Various studies have speculated that highly hydrophobic HCDR3 are thus less likely to create optimal paratopes (36,47,48). Schroeder and colleagues demonstrated that the mouse mature B cell repertoire uses D H RFs that are rich in the amino acids tyrosine and glycine (49).…”
Section: Cdr3 Length and Compositionmentioning
confidence: 99%
“…2) that preferentially bear BCRs with hydrophobic H chain CDR3 (HCDR3) regions (6). Skewing of hydropathicity profiles toward B cells with hydrophobic binding sites is unusual in mice and humans (7)(8)(9) and was not observed in littermates infected with SIV, sham controls, young pigs infected with helminthic parasites, or in newborn piglets (6). However, that study did not randomly sample B cell clones, so the size of the subpopulation could not estimated and the source of the expanded clones with regard to either V H gene usage or isotype expression was not identified.…”
Section: P Orcine Reproductive and Respiratory Syndrome (Prrs)mentioning
confidence: 99%